Pemanfaatan Lahan Perkotaan Untuk Aplikasi Budidaya Ikan Gabus Dengan Sistem Akuaponik - Farid Mudlofar; Rizal Akbar Hutagalung; Suparmin Suparmin; Agus Setiawan (Kapuas, 2021)
The need for fish food is not in line with the increasing land of densely populated residential areas, especially in the capital city of West Kalimantan province, Pontianak City. The development of Snakehead fish culture is very promising, when assessing economically the selling price of snakehead fish has a good market potential to improve the community's economy Pontianak City. The acuponic system is very relevant to be carried out in urban areas with the availability of narrow land, because the acuponic cultivation system is more effective in land use. The implementation of community service activities in the snakehead fish culture community with an aquaponic system aims to provide solutions for fish cultivation communities in densely populated areas to utilize residential land to improve the economy. The method of science and technology transformation is carried out through theoretical training on the prospects of snakehead fish farming with an acuponic system, how to make an aquaponic system installation, good ways of fish farming, snakehead fish production and sustainable vegetable crops. Next is the application of snakehead fish enlargement by using the aquaponic system and analyzing the snakehead fish farming business with the aquaponic system. Monitoring of water quality, feed, and growth of fish and plants is carried out every day. Monitoring the growth of weight and survival rates of fish and plants is done every month and evaluated the success of activities carried out at the end of the activity. During the mentoring activities not only carried out in technical activities, but also in institutional fish cultivators, so that an established, independent and productive entrepreneurial group was formed. Keywords: channa striata, aquaponic, land, limited